Answer:
1)
cubic units
2)
cubic units
Explanation:
Problem 1
Because our axis of rotation is not the x-axis, we must use the washer method, which is
.
If we plot the graphs of each function, we see that
is our outer function, and
is our inner function. If we set the equations equal to each other, we can get our bounds of integration where the equations intersect, which are
to
.
Taking into consideration our axis of revolution is
and NOT
, the x-axis, the outer radius would be
, and our inner radius would be
.
Putting everything together, we calculate the definite integral:
![\displaystyle A=\pi\int\limits^b_a \bigr[{\text{(Outer Radius)}^2-\text{(Inner Radius)}^2)}\bigr] \, dx\\\\A=\pi\int\limits^1_0 \bigr[(-2-x)^2-(-2-x^3)^2}\bigr] \, dx\\\\A=\pi\int\limits^1_0 \bigr[(x^2+4x+4)-(x^6+4x^3+4)}\bigr] \, dx\\\\A=\pi\int\limits^1_0 \bigr[x^2+4x-x^6-4x^3}\bigr] \, dx\\\\A=\pi\int\limits^1_0 \bigr[-x^6-4x^3+x^2+4x}\bigr] \, dx\\\\A=\pi\biggr[-(x^7)/(7)-x^4+(x^3)/(3)+2x^2\biggr]^1_0\\\\A=\pi\biggr[-((1)^7)/(7)-(1)^4+((1)^3)/(3)+2(1)^2\biggr]](https://img.qammunity.org/2023/formulas/mathematics/college/bh2zguovgtlaawnhq3tu3sgp91l2h66frc.png)
![\displaystyle A=\pi\biggr[-(1)/(7)-1+(1)/(3)+2\biggr]\\\\A=\pi\biggr[-(3)/(21)-(21)/(21) +(7)/(21)+(42)/(21)\biggr]\\\\A=(25\pi)/(21)\approx3.74\:\text{cubic\:units}](https://img.qammunity.org/2023/formulas/mathematics/college/tfbwt10kno4bpd9znre85w095khmi1euko.png)
Problem 2
The shell method for revolving the area between the two curves
and
about
is
where
.
By graphing the two equations, we can see that
is the upper function, and
is the lower function. If we set the two equations equal to each other and find the points of intersection, we can determine our bounds of integration. Since they intersect at points
and
, our bounds of integration will be
to
.
Since our axis of revolution is
and NOT
, the y-axis, we must account for this as indicated in the above equation.
Putting everything together, we can calculate the definite integral:
![\displaystyle A=2\pi\int\limits^b_a {(x-h)\bigr[f(x)-g(x)\bigr]} \, dx\\\\A=2\pi\int\limits^1_0 {(x-(-4))\bigr[√(x)-x\bigr]} \, dx\\\\A=2\pi\int\limits^1_0 {(x+4)\bigr[√(x)-x\bigr]} \, dx\\\\A=2\pi\int\limits^1_0 {\bigr[x√(x)-x^2+4√(x)-4x\bigr]} \, dx\\\\A=2\pi\int\limits^1_0 {\bigr[x^(3)/(2) -x^2+4x^{(1)/(2)}-4x\bigr]} \, dx\\\\A=2\pi\biggr[(2x^(5)/(2) )/(5)-(x^3)/(3)+(8x^(3)/(2))/(3)-2x^2\biggr]^1_0](https://img.qammunity.org/2023/formulas/mathematics/college/bx7ghhfmuzbxx48dbfbo7mkwhnr6jal68m.png)
![\displaystyle A=2\pi\biggr[(2(1)^(5)/(2) )/(5)-((1)^3)/(3)+(8(1)^(3)/(2))/(3)-2(1)^2\biggr]\\\\A=2\pi\biggr[(2)/(5)-(1)/(3)+(8)/(3)-2\biggr]\\\\A=2\pi\biggr[(2)/(5)+(7)/(3)-2\biggr]\\\\A=2\pi\biggr[(6)/(15)+(35)/(15)-(30)/(15)\biggr]\\\\A=2\pi\biggr[(11)/(15)\biggr]\\\\A=(22\pi)/(15)\approx4.61\:\text{cubic\:units}](https://img.qammunity.org/2023/formulas/mathematics/college/u451hsa7wf91z8j2haebpont8gv9z6fi51.png)